Modificações morfofisiológicas em plantas de milho submetidas a déficit hídrico - Martins, Juliano Dalcin (2010)
The use of no tillage can be an important technology to minimize the effects of the water deficit, for providing more water to the plants according to the maintenance of crop residues the soil surface. This technique reduces the amount of water evaporation from the soil, keeping it more humid, reducing fluctuations in soil temperature and, maintaining the water content in the soil higher. The work was to study indicators of water status of maize plants grown under different amounts of crop residues in coverage in irrigated condition and water deficit. Developed two experiment in the Experimental Department of Agricultural Engineering, Universidade Federal de Santa Maria (UFSM), RS, within a mobile coverage "Rainout shelter. We used a completely randomized, factorial with five replications. Factor A consisted of three volumes of straw on the soil surface: 0 (zero), 3 and 6 Mg ha-1 straw of oat (Avena strigosa Schreb). Factor B consisted of two management of irrigation water: (i) crop (maize plants were irrigated as needed throughout the development cycle), (ii) water deficit at vegetative stage V4 + deficit tesseling. The mobile coverage was triggered when rainfall, preventing that occurred obout in the experiment. We measured the water storage in the soil layers (0-10, 10-25, 25-55 and 55-85 cm depth) and indicators of plant water status: a potential minimum and the base of the leaf water, photosynthesis, stomatal conductance, transpiration rate and efficiency of water use, leaf area. There were no differences between treatments for the storage of water in the soil variables and indicators of plant water status. This inevitably occurred due to high amount of rainfall, even this does not occur directly in the experiment. The rains were 287% higher than the historical average, keeping the soil around the saturated mobile coverage raising the water level of water in the soil within the experiment, preventing the application of water deficit in the culture.